Sharing and valuing older Aboriginal people's voices about social and emotional wellbeing services: a strength-based approach for service providers. (3rd March 2020) - Gibson, Chontel; Crockett, Judith; Dudgeon, Pat; Bernoth, Maree; Lincoln, Michelle
Abstract: Objective: Over the last decade, the literature relating to older Aboriginal and Torres Strait Islander people's preferences for social and emotional wellbeing services has grown. However, little evidence exists in relation to older Aboriginal and Torres Strait Islander people's experiences of services relating to social and emotional wellbeing. This paper highlights older Aboriginal and Torres Strait Islander people's experiences of social and emotional wellbeing services in Australia and then uses these key findings of the research, along with the literature, to develop a strength-based approach for service providers. Methods: Yarning was the preferred research method for the older Aboriginal community. In total, 16 older Aboriginal people, including eight women and eight men participated in the research yarning sessions. A modified version of an existing thematic analysis process supported yarning members to participate in each stage of the research, including data analysis. Results: The themes emerging from the voices of the yarning members are they couldn't give a damn about them, You've got to get the right one and ticking the box . The themes focus on negative, positive and preferred experiences of social and emotional wellbeing service provision. Conclusion: The key findings and related literature contribute to the development of a strength-based approach, which supports the implementation of responsive and effective services that address Elders, older peoples and their communities' social and emotional wellbeing issues and aspirations.